ҚАРАҚАЛПАҚ ХАЛЫҚ ПРОЗАСЫ ЖАНРЛАРЫН КЛАССИФИКАЦИЯЛАЎДЫҢ ГЕЙПАРА МАШҚАЛАЛАРЫ - Алламбергенова, И. (SCIENCE and SOCIETY, 2020)
In the article there is told about some issues of classification of types of Karakalpak prose genre. In difference from legends and myths they are divided into various thematic types.